Професійний розвиток педагогів: теорії, концепції, підходи - Наталія Мукан; Ірина Грогодза (Pavlo Tychyna Uman State Pedagogical University, 2013)
Статтю присвячено дослідженню теоретичних основ професійного розвитку педагогів. Розглянуто теорії, концепції, підходи, покладені в основу професійного розвитку вчителів загальноосвітніх шкіл у провідних країнах світу (теорія системи, концепції акмеології, конструктивізму, педагогічної компетентності, андрагогічний, антропологічний, аксіологічний, інтеркультурний, структурно-функціональний підходи). Виокремлено засади, на яких ґрунтується професійний розвиток учителів загальноосвітніх шкіл у розвинутих англомовних країнах. Статья посвящена исследованию теоретических основ профессионального развития педагогов. Рассмотрены теории, концепции, подходы, положенные в основу профессионального развития учителей общеобразовательных школ в ведущих странах мира (теория системы, концепции акмеологии, конструктивизма, педагогической компетентности, андрагогический, антропологический, аксиологический, интеркультурный, структурно-функциональный подходы). Выделены принципы, на которых основывается профессиональное развитие учителей общеобразовательных школ в развитых англоязычных странах. The article is dedicated to the research on theoretical fundamentals of teachers' professional development. The authors have analysed theories, concepts, approaches underlying public school teachers' professional development in the leading countries of the world (theory of system, concepts of acmeology, constructivism, pedagogical competence, andragogical, anthropological, axiological, intercultural, structural-functional approaches). According to the theory of system and in the context of the structural-functional approach, professional development is considered to be a system, which comprises interrelated structural and functional components such as structure and subsystems, purpose and main objectives, functions, subjects, content and types of activities, integrity of development, dynamics of the system, nature and characteristics, conditions and factors. With the help of the axiological approach to the analysis of the phenomenon of public school teachers' professional development, the characteristics of the content of teachers' professional development, including not only knowledge and skills of a teacher, but also basic values of civilization in general and teaching profession in particular, the formation of a responsible attitude and commitment to educational activities, are studied. The use of the andragogical, anthropological approaches, and the concept of acmeology for studying public school teachers' professional development enables us to consider a teacher as an individual and specialist learning throughout life, and therefore going through certain stages of formation and development in the process of achieving teaching excellence. The competence approach involves the implementation of the ideas of target - oriented teachers' professional development, the formation of constitutive teacher's competences (knowledge, abilities, skills, values and attitudes), which contribute to the creation of an integrated personality, professional and citizen. On the basis of the conducted research, the common principles underlying public school teachers' professional development in the English-speaking countries have been determined. The main of them are: objective reality and ideas of the comprehensive projection of the educational process; social aspect of professional development and integration ties between science, ideology and realities of society's everyday life; principles of autonomy and diversity; constructivism, according to which knowledge is generated under the influence of internal (theories, ideas, interests, and needs of a person) and external (theory, experience, and interests of other people) factors; professional knowledge developing from various sources (empirical, technical, personal, ethical, ideological, interdisciplinary, knowledge of school subjects, social and political knowledge about the content of school education, knowledge of pedagogical subjects); the content of practical knowledge based on the research and professional development of teachers.